(untitled) - Adelson-Goldstein, Jayme (New York, 2007)
The Step-by-Step Lesson Plans provide strategies for conducting Student Book activities and applying the lesson to the multilevel classroom. It offers interleaved student book pages, detailed lesson plans with multilevel teaching strategies and tips, and a CD-ROM of printable multilevel grammar practice.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Problems, exercises,etc,Giáo trình dành cho sinh viên,Bài tập,bài giải,vv...